Uso de tela de sombreamento no cultivo de lisianto de corte - Silva, Mariana de Menezes (2014)
The cultivation of lisianthus is considered a recent activity when compared with the major cut flowers sold in the world, little is known about the full development of techniques for cultivation. The use of shade screens is a feature that can be used to increase productivity at the nursery because it alters the spectrum of solar radiation and the greenhouse microclimate, resulting in morphological and physiological responses in cultivation. Thus, the aim of this study was to evaluate the performance of varieties Lisianthus ABC 2-3 Blue, Lisianthus Allemade White and Lisianthus ABC Rose 2-3, in the environment with plastic cover as under coverage using the aluminized screens (TA), red screen (TV) and environment without screen (ST). The experiment took place in São Benedito, State of Ceará, in the period June to September 2013. Crop management was similar to the practices adopted by the undertaking form. The protected environment and the external environment (EXT) were monitored for twenty-four hours in the period of August 13 to September 1, 2013 as the temperature and relative humidity. The flow of solar energy was represented by kriging maps. Were evaluated: diameter of the flower bud (DB), number of flower buds (NB) and shaft thickness (ESP), as the rod size criteria , stem height (ALT) , full size (TR) were used and size commercial (TC). The hourly average in the period between 14h and 18h in the external environment was higher when compared to protected environments, TA and TV environments have average temperatures similar hourly throughout evaluated and the ST group was higher by 1°C when the TA and TV environments. The relative humidity was higher in protected environments as compared to the external environment. The ST group showed greater flux of solar energy. It was found that the protected environments interact significantly to the variable number of flower buds, rose variety had an average of 4.68 buttons in ST environment. We know the importance of the size criterion of the stem to add value to cut lisianthus in this way, the blue variety was more adapted to the conditions imposed by the TA environment, rose variety showed the best results in ST environment and the variety white under the conditions of the experiment, would be unfit for the cultivation of cut. The TV environment does not offer conditions conducive to satisfactory growth in the size of the rod.